The Influence of Dexamethasone on Apoptotic Genes Expression Changes in Rabies Virus-Infected Mouse Brain Tissue: The Influence of Dexamethasone in Rabies Virus-Infected Mouse Brain Tissue - Fekri, Matin; Fazeli, Maryam; Rasooli, Azadeh; Jamali, Niki; Bashar, Rouzbeh; Pourhossein, Behzad (Iranian Journal of Pharmaceutical Sciences, 2025)
Rabies is a severe public health issue, particularly in areas with limited vaccination rates. Despite significant progress in comprehending the illness and creating preventative methods, rabies poses a significant public health problem. Glucocorticoids like dexamethasone effectively reduce inflammation and immunomodulation, but their effects on viral infections, with specific reference to the central nervous system (CNS), are complex and unclear. This study focuses on the apoptosis of brain cells in NMRI (Naval Medical Research Institute) mice infected with a viral infection. Infected mice were randomly assigned to four groups (n=10 per group): a control group, a negative control group treated with dexamethasone, an untreated positive control group containing viral components, and a test group expressing viral components and treated with dexamethasone. FAT results showed that the virus components were present in the brain tissue of NMRI mice; intense positive staining was observed. AKT, BAX, and BCL2 expression were significantly lowered in rat brain tissue compared to untreated mice (p<0.05). This study demonstrates the significant change effected by dexamethasone in the pathway of brain cell death in mouse brain tissue. The findings of this study could have significant implications for the risk-benefit ratio of dexamethasone therapy in viral CNS infections and guide possibly more effective and safer treatment strategies in such conditions.